Gravity Data Interpretation in the Northern Edge of the Congo Craton, South-Cameroon - James Derek Fairhead; Charles T. Tabod; Jean Marie Tadjou; Yves N. Shandini (Anuário do Instituto de Geociências, 2010)
Gravity data in the southern Cameroon are interpreted to better understand the organization of underlying structuresthroughout the northern edge of the Congo craton. The Bouguer anomaly maps of the region are characterized by an elongated trending trending negative gravity anomaly which correspond to a collapsed structure associated with a granitic intrusion beneath the cente center of the region r of the region of the region and limited by fault systems. e applied 3D gravity modelling and inversion in order to obtain the 3D density structure of the area. Our result demonstrated that observed gravity anomalies in the region are associated to tectonic structures in the subsurface. The resulting model agrees with the hypothesis of the existence of a major continental collision zone between the Congo Craton and the PanAfrican belt. The presence of deep granulites structures in the northern part of the region expresses a continental collision.